Քննադատական հակասություններ՝ Սարոյանի ստեղծագործությունների բեմադրությունների շուրջ /1962-1991 թթ. բեմադրությունները/ - Անուշ Ասլիբեկյան (ՀՀ ԳԱԱ հրատ.)
Статья посвящена некоторым постановкам сарояновских произведений и обзору критических статей из книг и сборников о данных спектаклях. In this article we refer to somehow significant performances of Saroyan’s works that were staged in Armenian theatre during 1962-91 years and also about theatrical criticism of those performances that were includes in books and anthologies.
Keywords: Language and Literature; Dramatic representation; The Theater